Tinjauan Terhadap Delik Pencemaran Nama Baik yang Dilakukan dengan Media Internet Berdasarkan Peraturan Perundang-Undangan di Indonesia (Lex Jurnalica, 2011)
To the development of information technology and global trends as described above, included at least three elements essential requirement in the legal world, namely: (1) the legislation as an instrumental element that is expected to regulate the use and support the development of information technology, (2) Institutions war policy and oversee its implementation and control of the parties involved in the world of telematics as an element that is institutional, and (3) elements of the behavior of providers and users of information technology. Today, these elements have not been sufficiently developed in the life of society and the nation of Indonesia, so it might not be expected to actually support and reflect the characteristics of the information society as an ideal. Especially in terms of instrumental and institutional. What is Glare Libel and the Media How the Internet can become the Media Libel? What are the legal basis that can be used to trap the perpetrators of a crime or mempidana defamation committed through the medium of the Internet in Indonesia? How do I complete the offense of defamation case out of court? Form of research that writer used in this study normative research. Which is a form of normative research study conducted by searching or reviewing and analyzing library materials or materials that document readyKeywords: Delict, Internet, Regulation